Surface water erosion in the Mancotal river micro-basin in Jinotega Nicaragua, 1996 - 2015 (Nexo Revista Científica, 2021)
The Mancotal river micro-basin is an effluent from the Apanás reservoir that requires quantitative information about the rate of soil erosion. Soil erosion has a negative impact on the protection of the reservoir and has been intensified by the change in the use of forest-oriented land to subsistence farming. In this context, surface water erosion was estimated by using the “Revised Universal Soil Loss Equation (RUSLE)”. With this model, the factors of erosivity, erodibility, the length and gradient of the slope, coverage of soil and conservation practices were obtained. It was also found that there is an acceptable correlation (r² = 0.652), between the rainfall erosivity and the Modified Fournier Index (MFI) values, therefore, erosivity can be estimated using the MFI values. The results of the investigation showed that 94.46% of the micro-basin presented a high potential erosion, greater than 25 Ton/ha/ year.